2017
DOI: 10.1186/s13058-017-0884-8
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of neoadjuvant chemotherapy on tumor-infiltrating lymphocytes and PD-L1 expression in breast cancer and its clinical significance

Abstract: BackgroundThe effects of neoadjuvant chemotherapy on immune markers remain largely unknown. The specific aim of this study was to assess stromal tumor-infiltrating lymphocytes (TILs) and programmed death ligand 1 (PD-L1) protein expression in a cohort of breast cancer patients treated with neoadjuvant chemotherapy.MethodsUsing quantitative immunofluorescence, we investigated stromal TILs and PD-L1 protein expression in pre-treatment and residual breast cancer tissue from a Yale Cancer Center patient cohort of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
79
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 43 publications
14
79
2
Order By: Relevance
“…Discordance in PD‐L1 expression occurred more frequently in patients who had received neoadjuvant therapy, and was associated predominantly with positive PD‐L1 assay in TURB and negative assay at matched cystectomy. The effect of neoadjuvant therapy on PD‐L1 expression might be due to immune suppressive effects of chemotherapy, which has also been observed in breast and non‐small‐cell lung cancer …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Discordance in PD‐L1 expression occurred more frequently in patients who had received neoadjuvant therapy, and was associated predominantly with positive PD‐L1 assay in TURB and negative assay at matched cystectomy. The effect of neoadjuvant therapy on PD‐L1 expression might be due to immune suppressive effects of chemotherapy, which has also been observed in breast and non‐small‐cell lung cancer …”
Section: Discussionmentioning
confidence: 93%
“…The effect of neoadjuvant therapy on PD-L1 expression might be due to immune suppressive effects of chemotherapy, which has also been observed in breast and non-small-cell lung cancer. 9,10 Two recent studies investigated the concordance of different PD-L1 assays in urothelial cancer tissue microarrays, and found PD-L1 expression in 12-29% of samples. 11,12 Tretiakova et al found concordant PD-L1 assay outcome in matched primary urothelial carcinoma and lymph node metastasis in 90%.…”
Section: Discussionmentioning
confidence: 99%
“…The positive prognostic synergy observed in IBC tumors with both CD20 + TILs and PD-L1 + TILs might be the result of cooperation between the cellular and humoral immune responses. While cellular injury and immunogenic cell death induced by chemotherapy can lead to formation of new immunogenic epitopes, chemokine and cytokine secretion, antigen cross-presentation, activation of dendritic cells, and induction of tumor-specific cytotoxic T cells (cellular response) [31], the presence of B cells might enhance such T cell responses by producing antibodies against breast tumor antigens, stimulating cytokine and chemokine secretion, serving as local antigen-presenting cells, and organizing the formation of tertiary lymphoid structures that sustain long-term immunity (humoral response) [32]. As immunotherapy for breast cancer advances, it will be important to evaluate B cell presence, antigen specificity, and activity to determine the extent of B cell modulation and its relationship to patient response.…”
Section: Discussionmentioning
confidence: 99%
“…MMR and PD-L1 status may be influenced by prior neoadjuvant or adjuvant therapy as has been observed in both breast and colon cancer analyses 16 17 . Therefore, for primary pancreatic masses to include PDAC, it may be more desirable to perform such analysis on treatment-naïve specimens for which EUS-FNB is ideally suited to establish the molecular signature.…”
Section: Discussionmentioning
confidence: 94%